Cavitation tunnel tests for "The Princess Royal" model propeller behind a 2-dimensional wake screen. (15th January 2019) - Tani, Giorgio; Aktas, Batuhan; Viviani, Michele; Yilmaz, Naz; Miglianti, Fabiana; Ferrando, Marco; Atlar, Mehmet
Abstract: Propeller noise, especially in the presence of cavitation, is usually the main contributor to the acoustic signature of ships. Due to this fact, considerable efforts have been devoted to the study of underwater radiated noise induced by propeller cavitation during years: firstly, for military reasons; more recently, for other reasons relevant for merchant vessels, such as comfort on board and mitigation of the undesired impacts on marine fauna. Different approaches are available for the study and prediction of the cavitation noise, including statistical and CFD based methods as well as approaches based on model tests in cavitation tunnels or depressurised tanks. Amongst these approaches, the model test based approach is still the most reliable and commonly adopted method. However, when the aim of the model experiments is the prediction of noise radiated by a full-size ship, scale effects need to be analysed and taken into account to interpret model scale data and to achieve consistent prediction. Within this framework, each testing facility follows a procedure, which is developed through its own experience, theoretical considerations and possibly semi-empirical approaches to manage the different possible issues. The definition and harmonisations of the standards for the noise test and post-processing procedures of the propeller noise are still within the current tasks of the ITTC Specialist Committee on Hydrodynamic Noise and other standardization institutes. This results in more uncertainty compared to other more established tests such as resistance and self-propulsion. This paper presents the model scale tests carried out at the University of Genova (UNIGE) cavitation tunnel on the model propeller of the Newcastle University research catamaran, "The Princess Royal". Tests have been carried out using a 2D wake screen to approximate the real ship condition. The details of the experimental setup and results are presented and compared with the full-scale measurements in terms of cavitation and underwater radiated noise. This allows to explore the issues of the scale effects associated with these phenomena, focusing the attention on possible problems related to small-medium size cavitation tunnel.